(untitled) (Research, Society and Development, 2026)
The present study aimed to analyze, through a literature review, the scientific evidence regarding the benefits of inspiratory muscle training (IMT) in the elderly population. For this purpose, a search was carried out in the PubMed, PEDro, and SciELO databases, using descriptors related to the topic combined with Boolean operators, including articles published between 2020 and 2025, in Portuguese and English. Studies involving individuals aged 60 years or older were considered, including clinical trials and reviews, while duplicate or unavailable studies were excluded. At the end of the selection process, 17 studies were included for qualitative analysis. The results demonstrated that IMT promotes a significant increase in inspiratory muscle strength, mainly evidenced by improvements in maximal inspiratory pressure, in addition to contributing to reduced dyspnea, improved exercise tolerance, and, in some cases, enhanced functional capacity. It was also observed that the effects on pulmonary function were more modest in healthy elderly individuals, being more pronounced in those with respiratory impairments. Regarding quality of life, the studies indicated improvements mainly in physical aspects and general health perception. It is concluded that IMT represents a promising strategy in the context of aging, contributing to the maintenance of autonomy and quality of life, although further studies with greater methodological standardization are still needed to establish optimal protocols.